Photocatalytic hydrogen generation from a visible-light responsive metal–organic framework system: the impact of nickel phosphide nanoparticles. Issue 6 (25th January 2018) - Kampouri, Stavroula; Nguyen, Tu N.; Ireland, Christopher P.; Valizadeh, Bardiya; Ebrahim, Fatmah Mish; Capano, Gloria; Ongari, Daniele; Mace, Amber; Guijarro, Nestor; Sivula, Kevin; Sienkiewicz, Andrzej; Forró, László; et al.
Abstract : We showcase the key role of the co-catalyst when combined with MIL-125-NH2 towards the photocatalytic H2 generation. Abstract : Herein, we report the performance of a photocatalytic system based on visible-light active MIL-125-NH2 mixed with nickel phosphide (Ni2 P) nanoparticles. This combination boosts the H2 evolution rate to an outstanding value of 894 μmol h −1 g −1 under visible-light irradiation, which is among the highest H2 evolution rates reported to date for metal–organic frameworks (MOFs). The H2 generation rate exhibited by Ni2 P/MIL-125-NH2 is almost 3 times higher than that of the Pt/MIL-125-NH2 system, highlighting the impact of the co-catalyst on photocatalytic water splitting. Additionally, our system outperforms the Ni2 P/TiO2 system under UV-vis irradiation. The exceptional performance of Ni2 P/MIL-125-NH2 is due to the efficient transfer of photogenerated electrons from MIL-125-NH2 to Ni2 P, high intrinsic activity of Ni2 P and exceptional synergy between them. This system exhibits the highest apparent quantum yields of 27.0 and 6.6% at 400 and 450 nm, respectively, ever reported for MOFs.